Radiosynthesis and in-vitro identification of a molecular probe 131I-FAPI targeting cancer-associated fibroblasts - Tian, Yaxin; Jiang, Yanghongyan; Ma, Ping; Ma, Xiaowei; Du, Liang; Wang, Fengkui; Yu, Xiaodong (Frontiers in Oncology, 2024)
PurposeFibroblast activation protein (FAP) is highly expressed in the mesenchyme of most malignant epithelial tumors, while its expression is low in normal tissues. FAP inhibitors (FAPIs) bind specifically to FAP and are used for tumor-targeted diagnosis and therapy. The aim of this study was to radiosynthesize a novel molecular probe 131I-FAPI and evaluate its in-vitro targeting and biological characteristics.MethodsThe structurally modified FAPI was labelled with 131I through the chloramine-T method. The radiolabeling rate was then detected by thin-layer chromatography (TLC). The stability of 131I-FAPI was determined at PBS (room temperature) and serum (37°C). Its hydrophilicity was calculated by measuring its lipid-water partition coefficient. Pancreatic cancer PANC-1 cell line and glioma U87 cell line were cultured in vitro. Cell uptake assay was used to show the binding ability of 131I-FAPI. The CCK-8 assay was used to calculate the inhibitory effects of 131I-FAPI at different time points (4h, 8h, 12h, 24h, 48h) after comparing with the 131I and FAPI. The before-and-after-24h scratch areas of the two cells were determined in order to verify the effect of 131I-FAPI on the migration ability of the cells.ResultsThe radiolabeling rate was (84.9 ± 1.02) %. The radiochemical purity of 131I-FAPI remained over 80% in both 25°C PBS and 37°C serum. The value of the lipid-water partition coefficient was -0.869 ± 0.025, indicating the hydrophilic of the probe. The cellular uptake assay showed that U87 cells had a specific binding capacity for 131I-FAPI. In cell inhibition assays, the inhibitory effect of 131I-FAPI on U87 cells increased with time. The results of cell scratch assay showed that 131I-FAPI had the strongest inhibitory effect on the migratory ability of U87 cells compared with 131I and FAPI (P<0.001).Conclusion131I-FAPI was synthesized with good in-vitro stability and hydrophilic properties. It can be specifically bound by U87 cells. The proliferation and migration of U87 cells can be effectively inhibited. 131I-FAPI is promising to become a therapeutic probe.